Deciphering Green Promotion Attributes: A Conjoint Analysis of Tourists' Preferences in Greater Bandung - Suryana, Marceilla; Prawira, Mega Fitriani Adiwarna; Goeltom, Andar Danova Lastaripar; Susanto, Eko; Octaviany, Vany (Barista : Jurnal Kajian Bahasa dan Pariwisata, 2024)
The Greater Bandung area grapples with various challenges, including spatial planning, waste management, water resources, critical land, and transportation, all of which are intricately linked to sustainability concerns, particularly affecting tourism. To address these issues, it is crucial to understand tourists' preferences for green promotion attributes in destinations. This study employs conjoint analysis to discern tourists' perceptions of various destination attributes. Findings reveal that Greater Bandung tourists prioritize environmentally friendly tourism activities as the most significant destination image attribute, while ecologically friendly transportation ranks as the least important. Additionally, when assessing destination advertising attributes, environmentally friendly visuals hold more importance than environmentally friendly messaging. Tourists prioritize sustainable product packaging, while they consider the destination's tourist product color to be less significant. These findings underscore the importance of clear communication, ecolabeling, and environmentally friendly practices in promoting sustainable tourism in the Greater Bandung area. By understanding tourists' preferences, stakeholders can tailor promotional strategies to effectively convey the destination's green initiatives, thus enhancing its appeal and contributing to sustainable tourism development.